1999
DOI: 10.1007/s11745-999-0438-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms mediating lipoprotein responses to diets with medium‐chain triglyceride and lauric acid

Abstract: Medium-chain triglycerides (MCT) are often used in specialized formula diets or designer fats because of their special properties. Yet their influence on lipid metabolism is not completely understood. In this two-period cross-over study, the effects of MCT (8:0 + 10:0) in contrast to a similar saturated fatty acid (12:0) were compared. Eighteen healthy women ate a baseline diet [polyunsaturated (PUFA)/saturated fat = 0.9] for 1 wk. Then, they consumed test diets (PUFA/saturated fat = 0.2) for 4 wk. Monounsatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
1
13
1
Order By: Relevance
“…18) Their and our results suggest that the eŠects of MCTs on the serum cholesterol levels in healthy subjects resemble the eŠects of vegetable oil with a large amount of unsaturated fatty acids more than the eŠects of long-chain saturated fatty acids.…”
Section: Discussionsupporting
confidence: 56%
“…18) Their and our results suggest that the eŠects of MCTs on the serum cholesterol levels in healthy subjects resemble the eŠects of vegetable oil with a large amount of unsaturated fatty acids more than the eŠects of long-chain saturated fatty acids.…”
Section: Discussionsupporting
confidence: 56%
“…Reports of the effects of MCT feeding on circulating lipid levels in animal [22,26,27] and human studies [19,[21][22][23][24][25] have been well documented. Recent studies in our laboratory have shown that in humans, MCT oil in combination with phytosterols and flaxseed oil has the capacity to negate the deleterious effects of plain MCT feeding [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MCT have also been shown to increase circulating LDL cholesterol levels [23,24]. However, some studies have obtained different results demonstrating no effect of MCT on plasma triglycerides [23,24], as well as the capacity to decrease circulating triglycerides [25] in addition to improvements in plasma LDL and total cholesterol (TC) levels [22,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In a small, but well-designed, crossover trial, Tsai et al (1999) reported that plasma total cholesterol concentration was reduced by 8% (0.37 mmol/l) when women replaced 30 g of lauric acid (C12:0) with a mixture of caprylic (C8:0) and capric (C10:0) acids. There does not appear to be a strong effect on plasma HDL of substituting medium chain fatty acids for myristic (C14:0) and palmitic (C16:0) acids (Denke & Grundy, 1992;Cox et al, 1995;Temme et al, 1996;Tsai et al, 1999); however, participants in the present study had significantly lower HDL cholesterol concentrations when consuming the sheep's dairy products. Thus, the favourable improvement in lipoprotein-mediated cardiovascular risk associated with the lowering of total and LDL cholesterol during the sheepdairy diet was offset, somewhat, by the reduction in HDL cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Myristic acid (C14:0), which is abundant in cows' dairy fat, is the most cholesterolaemic fatty acid followed by palmitic acid (C16:0), and lauric acid (C12:0); whereas, stearic acid (C18:0) appears to have little cholesterol-raising effect (Katan et al, 1995;Kris-Etherton & Yu, 1997). The effects of caprylic (C8:0) and capric (C10:0) acids are not as well documented, but have been found to be less cholesterolaemic than lauric acid (Tsai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%